Peluang Imbuhan Pakan Herbal-Probiotik Komersial “Promix®” Sebagai Pengganti Antibiotic Growth Promoter (AGP) pada Ayam Pedaging yang Diberi Vaksin ND - Agnesia Endang Tri H. Wahyuni; Vinsa Cantya Prakasita; Thomas Emanuel Manggotu Nahak; Agustina Viktoria Tae; Jeffi Chandra; Ajiguna Ajiguna; Sruti Listra Adrenalin; Lynda Nugrahaning Imanjati; Ima Fauziah (Jurnal Sain Veteriner, 2019)
With the prohibition of the use of Antibiotic growth promotors (AGP) used in animal feed, especially in broilers, the use of feed additives such as herbs, probiotics, prebiotics, synbiotics or mixtures of some of these ingredients is currently widely used as feed replacements for AGP substitutes. One of the commercial feed additives that contain combinations herbal and probiotics is Promix®. In broiler maintenance, one vaccine that must be given is Newcastle Disease (ND) vaccine. The purpose of this study was to determine the role of supplementation of commercial feed combination of herbs and probiotics in broilers given ND vaccines. A total of 42 broilers were divided into two, group A (vaccinated with ND) and B (not vaccinated ND), each with 21 heads. Group A is divided into groups A1, A2 and A3 each with 7 heads. The A1 group is given only basal feed; A2 basal feed and AGP; A3 basal feed and Promix®. Group B is divided by B1, B2 and B3 same as group A before. Broilers are maintained for 5 weeks and weighing each week. All data obtained were statistically analyzed using One Way ANOVA and continued with Duncan's post hoc test. The results of this study were that the group of chickens given the ND vaccine and given supplements of Promix® had greater weight gain (P˂0.05) compared to the AGP and basal groups in the fifth week while in the group of chickens that were not given the ND vaccine but given supplement Promix® feed had greater weight gain (P˂0.05) compared to the AGP and basal groups in the fourth week. In the fifth week there was no significant difference (P˂0.05) between all feed groups in the group not given the ND vaccine. The conclusion of this study that feed additives contain combinations herbal and probiotics can replace AGP as feed additive in broiler. By giving ND vaccine the weight gain of the feed group plus Promix® showed a significant increase in weight gain.